Numerical investigation of flow boiling in double-layer microchannel heat sink - Ahmed, Shugata; Seder, Islam M.F.; Ab. Manaf, Hazli; Ahmed, Mirghani Ishak; Hawlader, Mohammad Nurul Alam (INSI Publications, 2014)
Double-layer microchannel heat sinks (DL-MCHS) are considered as an effective solution of temperature non-uniformity on the surface of microelectronic devices. However, only single-phase flow is analyzed so far in DL-MCHS. In this paper, numerical investigation has been carried out to observe the flow boiling phenomena in DL-MCHS. FLUENT ver. 14.5 has been used to simulate the multiphase flow in this particular heat sink. A mathematical model of the system has been provided. From the results, it is observed that two-phase heat transfer coefficient increases with increasing heat flux and decreases after achieving critical heat flux (CHF). For the considered channel, CHF is found to be550×〖10〗^4 Wm^(-2).Highest heat transfer rate during boiling is 6.4 W.